Deceased Donation Uterus Transplantation: A Review - Natasha Hammond-Browning; Si Liang Yao (Transplantology, 2021)
Uterus transplantation (UTx) offers women with absolute uterine factor infertility the option to gestate and birth their own biologically related child. The first birth following living donation UTx happened in 2014. The first birth following deceased donation happened in December 2017, with further successes since. Interest in deceased donation UTx is increasing. The authors established a database to track UTx clinical trials and outcomes. Utilising this database and existing literature, this article reviews the first reported cases of deceased donation UTx and outcomes, and drawing upon comparisons with living donor UTx, comments upon the future for this area of reproductive transplantation research. This is the first article to bring together the literature on deceased donation UTx procedures and outcomes.